Qualitative Analysis using HFACS Model on Factors Causing Risk-taking Behavior at Workplace - Rizky Yuli Ikhwanuddin; Zulkifli Djunaidi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: The risk of workplace accidents, according to the 2022 Indonesian National Occupational Health and Safety (OHS) Profile, is influenced by human factor in safety. This factor includes risk-taking behavior at workplace. One of the industrial sectors that needs a highlight in investigating risk-taking behavior is mining industry, which has 100% increase of workplace accidents in 2022. Objective: This paper explores several results from research which aims to identify factors causing risk-taking behavior at workplace. Method: Qualitative approach of a research is explored in this paper. The participants of this study are 283 employees of PT. XYZ Site A, a mining contractor company in Indonesia, ranging from managers, supervisors, and workers. The primary data of this paper was collected from the answers and reasons that the participants write in a questionnaire with open-ended questions, while the secondary data of this paper was taken from SMKP implementation documents and records obtained from PT. XYZ Site A. These data were then analyzed qualitatively using HFACS (The Human Factors Analysis and Classification System) Model. Result: As per HFACS analysis, factors causing risk-taking behavior at workplace are decision errors and perceptual errors (Unsafe Acts level), complacency, misplaced motivation, and lack of communication (Preconditions for Unsafe Acts level), inadequate supervision, failure to correct problem, and supervisory violations (Unsafe Supervisiion level), as well as resource management, organizational climate, and organizational process (Organizational Influences level) Conclusion: All levels of HFACS contribute risk-taking behavior at workplace, in which organizational influences level is the one whose all sublevels play roles in triggering such behavior. organization needs to increase its influence to its employees to not take risk at their works by improving resource management, organizational climate, as well as safe organizational processes.